Electrical detection of coherent spin precession using the ballistic intrinsic spin Hall effect - Choi, Won Young; Kim, Hyung-jun; Chang, Joonyeon; Han, Suk Hee; Koo, Hyun Cheol; Johnson, Mark (NATURE PUBLISHING GROUP, 2015)
The spin-orbit interaction in two-dimensional electron systems provides an exceptionally rich area of research. Coherent spin precession in a Rashba effective magnetic field(1,2) in the channel of a spin field-effect transistor(3,4) and the spin Hall effect(5-7) are the two most compelling topics in this area. Here, we combine these effects to provide a direct demonstration of the ballistic intrinsic spin Hall effect(8) and to demonstrate a technique for an all-electric measurement of the Datta-Das(3) conductance oscillation, that is, the oscillation in the source-drain conductance due to spin precession. Our hybrid device has a ferromagnet electrode as a spin injector and a spin Hall detector. Results from multiple devices with different channel lengths map out two full wavelengths of the Datta-Das oscillation. We also use the original Datta-Das technique with a single device of fixed length and measure the channel conductance as the gate voltage is varied. Our experiments show that the ballistic spin Hall effect can be used for efficient injection or detection of spin polarized electrons, thereby enabling the development of an integrated spin transistor.
Keywords: INJECTION